2013
DOI: 10.5539/ijef.v5n3p113
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability Reporting and Analysis of Sustainability Reports in Turkey

Abstract: Financial reports are the most important sources of information for financial information users. Investors, lenders, and other creditors use financial information in their decision making process. Therefore, governmental bodies of financial reporting have mandated disclosing of some financial reports (statement of financial position, statement of comprehensive income, and statement of changes in equity) for public interest. It has been stated that besides financial information, non-financial information is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 13 publications
2
22
0
4
Order By: Relevance
“…Later, some started to document economic, environmental and social aspects and their impacts on them, based on the triple bottom line approach (Maharaj and Herremans 2008: 36, Following the critical evaluation of G3 and G4, a short explanation is provided about the upcoming changes at the end of this section. Knebel and Seele (2015), Issakson and Steimle (2009) and Aktaş et al (2013) all based their research on reports using the GRI G3. The biggest advantage of GRI G3 was its completeness, while its biggest disadvantage lay in the use of an excessive amount of indicators, which made longitudinal comparison and benchmarking within the industry rather difficult.…”
Section: Definitions Reasons Aims and Expected Advantages Of Sustaimentioning
confidence: 99%
“…Later, some started to document economic, environmental and social aspects and their impacts on them, based on the triple bottom line approach (Maharaj and Herremans 2008: 36, Following the critical evaluation of G3 and G4, a short explanation is provided about the upcoming changes at the end of this section. Knebel and Seele (2015), Issakson and Steimle (2009) and Aktaş et al (2013) all based their research on reports using the GRI G3. The biggest advantage of GRI G3 was its completeness, while its biggest disadvantage lay in the use of an excessive amount of indicators, which made longitudinal comparison and benchmarking within the industry rather difficult.…”
Section: Definitions Reasons Aims and Expected Advantages Of Sustaimentioning
confidence: 99%
“…Analyzing quantity and quality levels of the reports from six Brazilian companies classified as Application Level A+, Leite Filho et al (2009) identified no traces of a good level of disclosure to justify such Application Level whatsoever. Adding to that, Aktas et al (2013) concluded that GRI's indicators are inconsistent within companies stating the same Application Level.…”
Section: Journal Of Management Researchmentioning
confidence: 99%
“…Companies that wish to build a sustainable image are keener on adopting the common practice of elaborating sustainability reports. According to Aktas, Kayalidere and Kargin (2013), reporting sustainability is a key process to inform stakeholders whether the firm is achieving sustainable growth and value for their interest. Stubbs, Higgins and Milne findings (2012) suggest that the route to encouraging greater and better quality uptake of sustainability reporting rests on stakeholders exerting pressure for better and more detailed disclosure from business firms.…”
Section: Introductionmentioning
confidence: 99%
“…Konar and Cohen (2001) state that major companies tend to voluntarily comply with environmental regulations and externally portray an image of being environmentally concerned, being rewarded in the marketplace for taking these actions. According to Aktas, Kayalidere and Kargin (2013), reporting sustainability is a key process to inform stakeholders whether the firm is achieving sustainable growth and value for their interest. Ross (1973) advocates that the agency theory resides on the situation where there are two forces and one of them (agent) acts in behalf of the other (principal), which may result in interest conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%